Makna Kata Taat dan Hormat dalam Efesus 6:1-3 - Tiur Imeldawati (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2019)
The first education obtained by a child is in the family and is obtained from parents. The tendency of children usually mimics in accordance with the example received from their parents. Every family usually has a tradition inherited from generation to generation in the form of values, and habits that unconsciously shape the character of the child. Families that fail to shape the character of children are usually families full of conflict or unhappy. The parents' heavy duty is to make sure family functions work as they should. Good character is a character that is taught in terms of words, behavior, patience, love, loyaltyand also in faith. Parents must be good figures for their children. This paper examines the meaning of the word of obedience and respect in Ephesians 6: 1-3 in contributing to the Christian education in the family.